2013
DOI: 10.1155/2013/209401
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Wide Conjunctival Flap and Conjunctival Autografting Techniques in Pterygium Surgery

Abstract: Pterygium is an abnormal fibrovascular tissue extending on the cornea which is a degenerative and hyperplastic disorder. A stromal overgrowth of fibroblast and blood vessels is accompanied by an inflammatory cell infiltrate and abnormal extracellular matrix accumulation. The surgical excision is the main treatment method of pterygium, but recurrence is the most common postoperative complication. In the present study, we aimed to compare the wide conjunctival flap and the conjunctival autografting techniques in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
1
15
0
4
Order By: Relevance
“…There are many 12 Predominantly, most of the studies comparing recurrence rates of free conjunctival autograft and conjunctival flap techniques have reported that results were similar. [16][17][18][19] Our results are in accordance with most of the literature with 6.1% and 6.6% recurrence rates for conjunctival autograft technique and conjunctival rotational flap technique respectively. No severe complication threatening vision was seen among the groups.…”
supporting
confidence: 88%
“…There are many 12 Predominantly, most of the studies comparing recurrence rates of free conjunctival autograft and conjunctival flap techniques have reported that results were similar. [16][17][18][19] Our results are in accordance with most of the literature with 6.1% and 6.6% recurrence rates for conjunctival autograft technique and conjunctival rotational flap technique respectively. No severe complication threatening vision was seen among the groups.…”
supporting
confidence: 88%
“…11 Aslan with 45 eyes observes rate of recurrence of pterygium following rotational flap surgery and auto conjunctival graft procedure (P=0.46) was comparable. 9 Kim observed statistically similar recurrence rate for auto and rotational flap 8% and 8.6% respectively. 10 By keeping view for future filtration surgery the harvesting site of transplant tissue might be inferior bulbar conjunctiva.…”
Section: Discussionmentioning
confidence: 60%
“…7,8 Conjunctival autograft transplantation in the form of free or rotational flap is also an effective surgical procedure that reduces the recurrence of pterygium and no statistical significant between two procedures. 9,10 Recurrence of pterygia usually occurs during the first 6 months. 11 Aslan with 45 eyes observes rate of recurrence of pterygium following rotational flap surgery and auto conjunctival graft procedure (P=0.46) was comparable.…”
Section: Discussionmentioning
confidence: 99%
“…Ancak %24-89 gibi yüksek nüks oranları nedeniyle alternatif cerrahi yöntemler geliştirilmiştir [14]. Günümüzde çeşit-li modifiye cerrahi yöntemler (amniotik membran transplantasyonu, konjonktival otogreft transplantasyonu, konjonktivalimbal otogreft transplantasyonu) ve adjuvan ajanlar (mitomisin-C, 5-florourasil, thio-tepa ve beta radyasyon) kullanılmaya başlan-mıştır [9,10].…”
Section: Discussionunclassified
“…Uzun yıllar uygulanan çıplak sklera ve primer konjonktiva kapatılma-sında oldukça yüksek nüks oranlarına rastlanmıştır [2]. Nüks oranlarını azaltmaya yönelik çeşitli modifiye cerrahi yöntemler kullanılmaya başlanmıştır [9,10]. Bu yöntemlerden konjonktivalimbal otogreft transplantasyonu, pterjium nüks oranlarının (%2-9) ve komplikasyon oluşumunun azaltılmasında en etkili yöntem olarak bildirilmiştir [11,12].…”
Section: Introductionunclassified